LIKASI PUPUK ORGANIK CAIR FERMENTASI URINE KELINCI (POCFERUCI) TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI DI WILAYAH TUNGKARAN KABUPATEN HULU SUNGAI SELATAN - Untung Santoso; Danang Biyatmoko (Universitas Lambung Mangkurat, 2022)
Hulu Sungai Selatan Regency is an agricultural area where the distribution of the economic sector which is dominated by the agricultural sector accounts for 46,68% of the regional PAD. This makes HSS Regency has the potential to become an agropolitan area supported by agribusiness. The Tungkaran area of Ulin Village with the majority of the population as farmers is currently developing the main farming crop, namely rice. Meanwhile, on dry land (gardens) chili plants and other vegetables are planted. The application of fertilization is a very important factor so that the vegetative growth and productivity of chili plants can increase. The use of inorganic fertilizers, besides being expensive, also has an impact on the lower quality of land and its dependence is increasing over time. Therefore, the use of liquid organic fertilizer fermented rabbit urinee (POCFERUCI) is an alternative solution in overcoming problems in the use of inorganic fertilizers. POCFERUCI fertilization affected the growth and production of chili plants and a fertilizer dose of 10 ml plant-1 gave the best response to all parameters of chili plant growth and production.